2002
DOI: 10.1111/1468-005x.00091
|View full text |Cite
|
Sign up to set email alerts
|

Women, social skill and interactive service work in telephone call centres

Abstract: This paper contributes to current debates about gender, work and skill in the service economy, focusing specifically on the case of women's employment in telephone call centres. The paper asks whether call centre employers are capitalising on women's 'feminine? social skills, and examines the degree to which these skills are being developed, acknowledged and recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 19 publications
3
118
0
12
Order By: Relevance
“…Selection for training beyond basic product and systems knowledge seems based on managers' stereotypical notions of women's suitability (Belt, 2002;Belt et al, 2002). Wider cultural cues may reinforce stereotypes.…”
Section: Supervisor Career Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection for training beyond basic product and systems knowledge seems based on managers' stereotypical notions of women's suitability (Belt, 2002;Belt et al, 2002). Wider cultural cues may reinforce stereotypes.…”
Section: Supervisor Career Supportmentioning
confidence: 99%
“…Although the call centre has been the subject of extensive study, both as a phenomenon in its own right and as a research site for testing diverse theories (Deery and Kinnie, 2004), the literature on gender remains surprisingly limited (Russell, 2008) and early promising studies (Belt, 2002;Belt et al, 2000Belt et al, , 2002 have not been built upon. Many questions remain unanswered leaving contradictory representations of the opportunities call centres provide for women.…”
Section: Introductionmentioning
confidence: 99%
“…In their place, the re-designed work space is used as a site where management attempts to replace informal nonwork self expression with a sanctioned and orchestrated version of non-work activity that can appear to serve the employee's need to express the other aspects of self: team Because what can constitute fun time also encompasses the types of behaviour that are also thought necessary to maximize positive responses from customers, such as 'smiling down the phone' or 'flirty selling' (Belt et al, 2002), management is actually pursuing a form of disguised culture training to further socialise a range of normatively embodied branding displays.…”
Section: Accepted For Economic and Industrial Democracy Volume 31 (I)mentioning
confidence: 99%
“…Similarly, Higgs (2004) found differences between age and gender groups in terms of performance of agents in call centres in the United Kingdom. A study by Belt et al (2002) indicated that females are recruited specifically by call centre employers in part because they are deemed to "naturally" possess the kinds of communication skills required in call centres, and that they expect women to perform emotional labour over the phone, using their femininity to secure competitive advantage. Thus, it may be that the demographic nature of the sample may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%